Gut microbiota and metabolism - İlhan, Nevin (My University, 2018)
Objectives: The intestine of a healthy human harbors over 100 trillion cells that have a symbiotic relationship with thehost, and they play a part in important metabolic, systemic, and immunologic functions. The human gut microbiotabegins to take shape in the fetal life, and it achieves adult-like properties by the age of 2–3 years after being influencedby the type of delivery, feeding with either breast milk or formula, antibiotic use, as well as many environmental factorsleading to dysbiosis. The important role that the gut microbiota plays in human metabolism and health, as well asidentification of specific microorganisms that play role in various metabolic processes have encouraged researchers toinvestigate metabolism of dietary components and some metabolites produced by the host in particular. Importantmetabolic functions of the gut microbiota include fermentation of complex carbohydrates that escape digestion; variouspolyphenols consumed in the diet; fats, amino acids, and proteins; deconjugation of bile acids; and synthesis ofvitamin K and several components of vitamin B. This review aims to discuss the relationship between gut microbiotaand metabolism of biochemically important macromolecules, flavonoids, and gases. In addition, a summary of the upto-date information on this subject is presented with the aim of emphasizing the importance of microbiota.
Keywords: Biyoloji; Biyokimya ve Moleküler Biyoloji